TINJAUAN YURIDIS PRIVACY POLICY PADA ONLINE STORE TERKAIT PERLINDUNGAN DATA PRIBADI BERDASARKAN KETENTUAN DI NEGARA MALAYSIA DAN INDONESIA - Mody Malinda (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2017)
Mody Malinda, Dr. Bambang Winarno Winarno, S.H., M.S., M. Zairul Alam, S.H., M.H Fakultas Hukum Universitas Brawijaya Email: modymalinda95@gmail.com A. Abstrak Penulisan jurnal ini bertujuan untuk mengetahui bagaimana perbedaan ruang lingkup ketentuan tentang perlindungan data pribadi pengguna  Online Store di Malaysia dalam  Malaysia Personal Data Protection Act 2010 dan di Indonesia dalam Undang-Undang Republik Indonesia Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi Dan Transaksi Elektronik dan Peraturan Pemerintah Nomor 82 Tahun 2012 Tentang Penyelenggaraan Sistem dan Transaksi Elektronik dan juga bertujuan untuk mengetahui analisa perlindungan data pribadi pengguna Online Store dalam privacy policy pada website Shopee, Lazada dan Qoo10 apabila dikaitkan dengan Malaysia Personal Data Protection Act 2010, Undang-Undang Republik Indonesia Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi Dan Transaksi Elektronik dan Peraturan Pemerintah Nomor 82 Tahun 2012 Tentang Penyelenggaraan Sistem dan Transaksi Elektronik. Jurnal ini disusun dnegan metode penelitian yuridis normatif dengan pendekatan Perundang – Undangan dan pendekatan perbandingan hukum. Berdasarkan hasil penelitian diketahui bahwa Ketentuan hukum mengenai perlindungan data pribadi pengguna Online Store dalam Malaysia Personal Data Protection Act 2010 lebih menjamin privasi pemilik data. Dari Online Store Shopee, Lazada dan Qoo10 dapat diketahui bahwa sebagaian besar sudah memenuhi standar ketentuan perlindungan data pribadi di negara Malaysia dalam Malaysia Personal Data Act 2010 dan ketentuan perlindungan data pribadi di Indonesia yaitu dalam Undang-Undang Republik Indonesia Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi Dan Transaksi Elektronik dan dan Peraturan Pemerintah No. 82 Tahun 2012 tentang Penyelenggaraan Sistem dan Transaksi Elektronik Kata Kunci: Informasi dan Transaksi Elektronik, Privacy Policy, Privasi, Perlindungan data pribadi, Data Pribadi. JURIDICAL REVIEW ON PRIVACY POLICY ON ONLINE STORE RELATED TO THE PROTECTION OF PERSONAL DATA BASED ON THE PROVISIONS IMPLEMENTED IN MALAYSIA AND INDONESIA.   Mody Malinda, Dr. Bambang Winarno Winarno, S.H., M.S., M. Zairul Alam, S.H., M.H   Faculty of  Law Brawijaya University   Email: modymalinda95@gmail.com ABSTRACT This research aimed at investigating the difference of provisions concerning the protection of personal data of the user of online in Malaysia’s Personal Data Act 2010 and that of Indonesia as contained in Law of the Republic of Indonesian 19 years on the  amendment of Law  number 11 year 2008 about Electronic Information and Transaction and Government Regulation Number 82 year 2012 about the administration of electronic systems and transaction. It also aimed at investigating the analysis of the personal data protection of the users  of online store in privacy policy on the websites of Shopee, Lazada and Qoo10 when compared with  Malaysia’s  Personal Data Protection Act  2010, The Law of The Republic of Indonesia number 19 year 2016 about the amandement of Law number 11 year 2008 on Electronic Information and transaction, and Goverment Regulation number 82 year 2012 about the administration of electronic system and transaction. The research design employed in this study was normative juridical with statute and comparative approaches. The result og the study shows that legal provision on the personal data protection of the online stores users in Malaysia Personal Data Protection Act 2010 gives  more privacy to the owner of the data. It is also found out that online stores such Shopee. Lazada and Qoo10  have met the standart of protection of personal data protection in Malaysia as contained in Malaysia Personal Data Act 2010. In Indonesia, the personal data protection is contained in The Law of the Republic of Indonesia number 19 year 2016 on the amandement of Law number 11 year 2008 on Electronic Information and Transaction the Goverment Regulation number 82 year 2012 on the Administration of Electronic System and Transaction Keywords: Electronic System and Transaction, Privacy Policy, Privacy, Personal Data Prtection, Personal Data